Ukuran Dewan sebagai Moderator: Memahami Praktik Lingkungan di Indonesia - Febryanti Simon; Etty Muwarningsari; Maria Stefani Osesoga (Society, 2024)
Global warming, driven primarily by carbon emissions, poses a critical challenge worldwide, including in Indonesia. In response, the Indonesian government issued Law No. 71 of 2021 to mitigate risks and promote carbon emission reduction. This study examines the influence of media exposure, managerial ownership, and industry type on carbon emission disclosure (CED), employing a quantitative design with purposive sampling of 66 companies from 2020-2022, resulting in 198 data points. CED is assessed through direct greenhouse gas (GHG) emissions, indirect emissions from electricity, and other GHG emissions. Findings reveal an adjusted R-square of 53.9%, with media exposure and industry type significantly impacting CED positively. The study underscores the importance of organizations adopting carbon-friendly initiatives to reduce emissions in business operations. It highlights the need for stronger governmental regulations to enhance corporate awareness and compliance with carbon disclosure practices.